The Opinion Paragraph in the Auditor’s Reports: The Bane of Auditing - Nkechinyelu, Belonwu Florence; Modum, Uche (Archives of Business Research, 2018)
The major threat in the accounting profession around the globe is the problem of corporate business failure. No doubt, strict efforts have been put in place to combat the problem of corporate business failure as well as limit the expectation gap, but all to no avail. At different stages and years, the opinion paragraph was changed severally; there were also conflicts to change the phrase from the term ‘fairly present’ to ‘presents fairly’ because fairness is a term that is imprecise. It was in a bid to proffer solution to the existing problems and hence narrow the expectation gap that suggestion (recommendation) was made to revert back to the previously used wordings of the opinion paragraph which were: “We certify that the above balance sheet (financial statement) in our opinion is a correct statement of the financial position of the company as of 31st Dec xxx and the accompanying profit and loss statement is correct”